EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SELF INSTRUCTION UNTUK MEREDUKSI STRES AKADEMI PADA PESERTA DIDIK KELAS XI MIPA DI SMAN 2 PURWAKARTA - shrisma handakusuma; Asep Samsudin; Muhammad Rezza Septian (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
The phenomenon of academic stress that occurs among students will greatly disrupt the conditions in the learning process. Academic stress has a negative effect on physiological and psychological. This study aims to test whether group guidance with self-instruction techniques is effective in reducing academic stress experienced by students. The method used is a quasy experiment using a noneqivalent control group design. The sample in this study was selected using a purposive sampling technique with a sample of 18 people divided into 2 groups, namely the control group and the experimental group. The measuring tool in this study uses an academic stress instrument made by the researcher and refers to Hans Selye's theory. Data processing in this study uses a non-parametric Wilcoxon Signed Ranks test obtained using SPSS ver 26. Based on the results of data analysis using the Wilcoxon Signed Ranks obtained the Asymp probability number. Sig (2-tailed) 0.008 < 0.05 so that H0 is rejected and Ha is accepted. This means that group guidance with effective self-instruction techniques to reduce academic stress in class XI Mipa students at SMAN 2 Purwakarta.